2022
DOI: 10.1371/journal.pone.0274697
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disease relapses: A cross-sectional study of the associated factors and socioeconomic inequalities during the COVID-19 pandemic in Peru

Abstract: To investigate the prevalence, associated factors and socioeconomic inequalities in chronic disease relapses (CDR) during 2020 in Peru. MethodsA secondary analysis was made of the National Household Survey on Living Conditions and Poverty (ENAHO) 2020. Participants older than 18 years who suffered from a chronic disease and with information about the occurrence of a CDR in the last 4 weeks prior to the survey were included. Adjusted prevalence ratios (aPRs) were estimated to determine the associated factors. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Similar to older people, it is likely that participants with a chronic disease were more concerned and anxious about the prevention of COVID-19, as they are considered a risk group. [64][65][66] It should be noted that, in Peru, people with a chronic disease and a low educational level and economic status have difficulties in accessing health services, 67 and, therefore, had less knowledge about preventive measures for COVID-19. In addition, people with chronic diseases and low resources are more likely to take a medication that is recommended to treat or prevent any symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to older people, it is likely that participants with a chronic disease were more concerned and anxious about the prevention of COVID-19, as they are considered a risk group. [64][65][66] It should be noted that, in Peru, people with a chronic disease and a low educational level and economic status have difficulties in accessing health services, 67 and, therefore, had less knowledge about preventive measures for COVID-19. In addition, people with chronic diseases and low resources are more likely to take a medication that is recommended to treat or prevent any symptom.…”
Section: Discussionmentioning
confidence: 99%
“…This health impact has led to a collapse in healthcare systems, resulting in a higher number of relapses of chronic diseases such as diabetes mellitus and hypertension due to increased demand and saturation of healthcare services for their management [5]. In response, access to healthcare services through telemedicine has become a primary tool for clinical management, impacting public health that was previously limited to very specific scenarios [6].…”
Section: Introductionmentioning
confidence: 99%
“…Older and female travelers were more likely to be more concerned about taking public transport during the COVID pandemic ( Shelat et al, 2022 ), and female women had a higher level of fear of infection than males and thus reduced even more their public transport usage ( Schaefer et al, 2021 ). In addition, education level not only contributes to the heterogeneity of COVID-19 infection ( Magesh et al, 2021 ; Visconti-Lopez et al, 2022 ), but also decreases the use of public transport ( Almlöf et al, 2021 ). Schaefer et al (2021) suggested that car use has increased in particular by residents of metropolitan areas, while it has decreased by residents of less densely populated areas in the region.…”
Section: Introductionmentioning
confidence: 99%